PENERAPAN UMUR SIMPAN SARI WORTEL PADA BIAYA PENYIMPANAN SELAMA PEMASARAN - Rekna Wahyuni (Fakultas Pertanian Universitas Yudharta Pasuruan, 2011)
ABSTRACT: Research target is to know shelf life of carrot juice. Knownly by shelf life knowable carrot juice hence the way of correct handling for it’s storage cost and carrot juice during marketing activity. ASLT method used in shelf life determination to use degradation of beta karoten and acidity (pH) parameter. Shelf life of carrot juice at low temperature (10 °C) is 62 days and at room temperature (± 27 °C) is 38 days. Storage applying at low temperature and room temperature for marketing of carrot juice in Pusat Oleh-oleh Khas Malang ”Caprina”, with storage capacities 630 bottles will bring consequence of storage cost. Storage cost of carrot juice at low temperature (10 °C) per month is Rp.262.133,00 while expense of per bottle of during one week is Rp.103,45. Storage cost of carrot juice at room temperature (± 27 °C) is Rp.8.333,00/ month while expense of per bottle during one week is Rp.9,92. This result can be used for consideration of price of sale of carrot juice.